Sasha Sokolov : the life and work of the Russian "proet" - Napolitano, Martina (Literatur und Kultur im mittleren und östlichen Europa ;, 2022)
Martina Napolitano explores the poetics of one of the most significant Russian authors of the 20th century. Sasha Sokolov's oeuvre represents a milestone in the development of Russian literature; his legacy can be traced in most prose and poetry appearing in post-Soviet Russia. Taking as point of departure the studies and analyses written so far and considering the new suggestions contained in Sokolov's last published book Triptych (2011), Napolitano further examines the keystones and the theoretical framework that arise from a close reading of Sokolov's works, trying to systematize the findings into what can be considered as a structured authorial theory of literary creation. The study demonstrates how Sokolov's oeuvre cannot be fully understood but within the widened perspective of inter-artistic creation: in fact, the writer, a "failed composer", as he admits, in his literary work has tried to draw natural and spontaneous connecting lines between the artificially categorized realms of art (word, sound, painting, performance). Finally, the book sets forth the first solid analysis of Sokolov's concept of proeziia, not merely a genre nor style of his own invention, but a more significant theoretical reflection of the writer about the role and value of literature, art, creation, and finally beauty